NUMERICAL ANALYSIS OF THE EFFECT OF THE NUMBER OF TURBINE BLADES ON WIND TURBINE CHARACTERISTICS AXIS HORIZONTAL NACA 4412 - Januar Ibrahim (Universitas Muhammadiyah Semarang, 2022)
The wind turbine is a device that can convert the kinetic energy in the wind into electrical energy. Wind turbine efficiency and performance depend on the design and angular shape of the wind turbine itself. The wind turbine used for analysis is a horizontal-axis wind turbine. This wind turbine performance analysis uses the Computational Fluid Dynamics (CFD) simulation method so that it can reduce the time and cost required. Aerodynamic simulations on airfoils used at the wind turbine angle are carried out to determine the aerodynamic characteristics of the airfoils used. Airfoil NACA 4412 is used as the basic form of the corner wind turbine. In conducting this research, computational simulation experiments on the design of the Horizontal Axis Wind Turbine NACA 4412 wind turbine by varying the number of turbine blades, 2 blades, 3 blades, and 4 blades and to find out which variant produces a greater torque and efficiency. Based on the simulation results, the 2-blade turbine gets the highest torque at TSR 6, which is 3,167 N/m with an efficiency of 53.3%, the 3-blade turbine gets the highest torque at TSR 5, which is 3,334 N/m with an efficiency of 46, 8% then the variation with the number of 4 blade blades gets the highest torque and efficiency among other variations, at TSR 5, which is 4.201 N/m with an efficiency of 58.9%.